IMPACT OF PHILIPPINES’ WITHDRAWAL FROM INTERNATIONAL CRIMINAL COURT ON CRIME AGAINST HUMANITY INVESTIGATION IN PHILIPPINES - Aisyah Jasmine Yogaswara (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract Rodrigo Roa Duterte is the incumbent president of the Philippines who was inaugurated on June 30th 2016 and initiated the War on Drugs Operation to eradicate drug abuse in the Philippines one day after his inauguration. The operation gave authorization to the members of Philippines National Police to ‘neutralize’ or kill suspects of illegal drugs dealers and users. The operation also related to other crime such as rape, imprisonment, and torture. The crimes are committed as part of a widespread and systematic attack directed against the civilian population as therefore it can be qualified as crimes against humanity. Philippines’ status as a state party to Rome Statute gives ICC the chance to prosecute Philippines’ nationals if they committed crimes against humanity. However, after the ICC Prosecutor initiated preliminary examination on the related case, Philippines deposited its instrument of withdrawal from the Rome Statute. The purpose of this research is to find out the legal effect of Philippines withdrawal toward ICC’s process of preliminary examination, investigation, and trial, and whether ICC have any jurisdiction over crimes against humanity that is committed after Philippines’ withdrawal becomes effective. Keywords: Crimes Against Humanity, International Criminal Court, Rome Statute Abstrak Rodrigo Roa Duterte menjabat menjadi Presiden Filipina pada tanggal 30 Juni 2016 dan memulai operasi pemberantasan narkotika yang disebut War on Drugs Operation sehari setelahnya. Operasi tersebut memberikan izin bagi Polisi Nasional Filipina untuk melakukan penembakan di tempat atas tersangka pengguna dan pengedar narkotika. Selain itu, terdapat kejahatan lain terkait operasi tersebut di antaranya pemerkosaan, penyiksaan dan penahanan tanpa proses hukum. Kejahatan-kejahatan tersebut dilakukan secara meluas, sistematis dan ditujukan pada populasi sipil yang menjadikannya dapat dikualifikasikan sebagai kejahatan terhadap kemanusiaan. Status Filipina sebagai negara pihak dalam Statuta Roma menjadikan ICC memiliki kewenangan untuk mengadili warga negara Filipina yang melakukan kejahatan terhadap kemanusiaan. Namun, setelah Jaksa Penuntut ICC memulai pemeriksaan pendahuluan atas War on Drugs Operation, Filipina melakukan penarikan diri dari Statuta Roma. Tujuan dari penulisan tugas akhir ini adalah untuk mengetahui bagaimana pengaruh penarikan diri Filipina dari Statuta Roma terhadap pemeriksaan pendahuluan yang sedang dilakukan dan apakah ICC memiliki yurisdiksi atas kejahatan terhadap kemanusiaan yang masih terjadi di Filipina pasca penarikan dirinya berlaku efektif. Kata kunci: Kejahatan Terhadap Kemanusiaan, Mahkamah Pidana Internasional, Statuta Roma